Successful treatment of carbohydrate deficient glycoprotein syndrome type 1b with oral mannose. Issue 4 (1st October 2001) - Hendriksz, C J; McClean, P; Henderson, M J; Keir, D G; Worthington, V C; Imtiaz, F; Schollen, E; Matthijs, G; Winchester, B G
Abstract : An Asian girl presented with failure to thrive, congenital hepatic fibrosis, protein losing enteropathy, and hypoglycaemia. Phosphomannose isomerase activity in skin fibroblasts was reduced. She is homozygous for a mutation, D131N, in the phosphomannose isomerase gene ( PM1 ), consistent with the diagnosis of carbohydrate deficient glycoprotein syndrome type 1b. She responded to oral mannose treatment.